Effects of Perioperative Probiotics and Synbiotics on Pancreaticoduodenectomy Patients: A Meta-Analysis of Randomized Controlled Trials - Tang, Gang; Zhang, Linyu; Tao, Jie; Wei, Zhengqiang (Frontiers in Nutrition, 2021)
Post-pancreaticoduodenectomy infections cause mortality, morbidity, and prolonged antibiotic use. Probiotics or synbiotics may be advantageous for preventing postoperative infections, but their benefits on pancreaticoduodenectomy outcomes are controversial. This study evaluated the efficacy of probiotics and synbiotics in pancreaticoduodenectomy. The Embase, Web of Science, PubMed, and Cochrane Library databases were comprehensively searched for randomized controlled trials (RCTs) that evaluated the effects of probiotics or synbiotics on pancreaticoduodenectomy as of April 16, 2021. Outcomes included perioperative mortality, postoperative infectious complications, delayed gastric emptying, hospital stay length, and antibiotic-use duration. The results were reported as mean differences (MDs) and relative risks (RRs) with 95% confidence intervals (CI). Six RCTs involving 294 subjects were included. Probiotic or synbiotic supplementation did not reduce the perioperative mortality (RR, 0.34; 95% CI, 0.11, 1.03), but reduced the incidences of postoperative infection (RR, 0.49; 95% CI, 0.34, 0.70) and delayed gastric emptying (RR, 0.27; 95% CI, 0.09, 0.76) and also reduced the hospital stay length (MD, −7.87; 95% CI, −13.74, −1.99) and antibiotic-use duration (MD, −6.75; 95% CI, −9.58, −3.92) as compared to the controls. Probiotics or synbiotics can prevent infections, reduce delayed gastric emptying, and shorten the hospital stay and antibiotic-use durations in patients undergoing pancreaticoduodenectomy. These findings are clinically important for promoting recovery from pancreaticoduodenectomy, reducing the incidences of antibiotic resistance and iatrogenic infections, and reducing the medical burden.